Security for Microsoft Windows system administrators : introduction to key information security concepts - Rountree, Derrick (Syngress, 2011)
It's no longer just a buzz word: "Security" is an important part of your job as a Systems Administrator. Most security books are aimed at security professionals, but Security for System Administrators is written for System Administrators. This book covers the basics of securing your system environment as well as security concepts and how these concepts can be implemented practically using common tools and applications. Whether you are new to this profession or have been in the field a while, you'll find valuable information in each chapter. The book's examples will focus on Windows Server 2008.